MicroRNA detection using light-up aptamer amplification based on nuclease protection transcription. Issue 14 (26th January 2022) - Hong, Yoonseo; Kim, Do-Eun; Park, Yu-Jin; Kim, Dong-Myung; Byun, Ju-Young; Shin, Yong-Beom
Abstract : Here, we report a simple nuclease protection transcription assay which combines nuclease protection assay and transcription-assisted light-up aptamer amplification for detecting miRNAs with great sensitivity. Abstract : The quantification of microRNAs (miRNAs) is important because the miRNA expression level is closely associated with the occurrence and development of diseases. Here, we report a simple nuclease protection transcription assay which combines nuclease protection assays and transcription-assisted light-up aptamer amplification for detecting miRNAs with great sensitivity.